(untitled) (International Journal of Nursing Education, 2024)
Aim This study sought to measure nursing faculty’s perceptions regarding the value of obtaining the CNE®/ CNE®n specialty certification. There is limited research surrounding efforts to improve perceived extrinsic and intrinsic values of certification and even less documentation on identifying a link between student learning outcomes and instruction by CNE®/CNE®n faculty.Methods Participants were recruited from a private college located in X, where only 16% of the 58 full and part- time academic nurse educators possess the Certified Nurse Educator® (CNE®)/Certified Nurse Educator® Novice (CNE®n) specialty certification. An online PVCT-12 survey was conducted pre- and post-CNE preparatory course to investigate changes in extrinsic and intrinsic perceived values of obtaining certification. Participants were also surveyed post-prep course to determine intent and timeframe for testing.Results: The study increased the number of full and part time academic nurse faculty with the CNE®/ CNE®n certification from 16% to 24%. There was also an increase in the perceived value of the certification, more notably in the extrinsic value category.Conclusion: Understanding these perceptions and motivators for certification can guide institutions in supporting faculty to increase their credentialed nurse educators. This study should be repeated with a larger population of nursing faculty across multiple academic institutions to produce more generalizable results. Future research should focus on identifying a link between improved student learning outcomes and instruction by CNE®/CNE®n faculty to further increase the extrinsic value of certification.